2020
DOI: 10.1101/2020.07.17.209767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unpicking the mysterious symbiosis ofMycoplasmain salmonids

Abstract: Lacking a peptidoglycan cell wall, mycoplasmas are the smallest self-replicating life forms. Members of this bacterial genus are known to parasitise a wide array of metazoans including vertebrates. Whilst much research has been significant targeted at parasitic mammalian mycoplasmas, very little is known about their role in other vertebrates. In the current study, we aim to explore the biology and evolution of Mycoplasma in salmonids, including cellular niche, genome size structure and gene content. Using Fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Due to its small compact genome and limited biosynthesis capacities, Mycoplasma typically forms obligate parasitic or commensal relationships with its host to obtain necessary nutrients such as amino acids, fatty acids and sterols [67]. Recent shotgunmetagenomic sequencing of the Atlantic salmon Mycoplasma revealed that it is closely related to Mycoplasma penetrans [33,68]. It was suggested that the presence of ribo avin encoding genes and lack of pathogenicity factors in the metagenome-assembled Mycoplasma genome is indicative of a symbiotic relationship between the Mycoplasma and Atlantic salmon [68].…”
Section: Core Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its small compact genome and limited biosynthesis capacities, Mycoplasma typically forms obligate parasitic or commensal relationships with its host to obtain necessary nutrients such as amino acids, fatty acids and sterols [67]. Recent shotgunmetagenomic sequencing of the Atlantic salmon Mycoplasma revealed that it is closely related to Mycoplasma penetrans [33,68]. It was suggested that the presence of ribo avin encoding genes and lack of pathogenicity factors in the metagenome-assembled Mycoplasma genome is indicative of a symbiotic relationship between the Mycoplasma and Atlantic salmon [68].…”
Section: Core Microbiotamentioning
confidence: 99%
“…Recent shotgunmetagenomic sequencing of the Atlantic salmon Mycoplasma revealed that it is closely related to Mycoplasma penetrans [33,68]. It was suggested that the presence of ribo avin encoding genes and lack of pathogenicity factors in the metagenome-assembled Mycoplasma genome is indicative of a symbiotic relationship between the Mycoplasma and Atlantic salmon [68].…”
Section: Core Microbiotamentioning
confidence: 99%
“…Due to its small compact genome and limited biosynthesis capacities, Mycoplasma typically forms obligate parasitic or commensal relationships with its host to obtain necessary nutrients such as amino acids, fatty acids and sterols [67]. Recent shotgun-metagenomic sequencing of the Atlantic salmon Mycoplasma revealed that it is closely related to Mycoplasma penetrans [33,68]. It was suggested that the presence of ribo avin encoding genes and lack of pathogenicity factors in the metagenome-assembled Mycoplasma genome is indicative of a symbiotic relationship between the Mycoplasma and Atlantic salmon [68].…”
Section: Core Microbiotamentioning
confidence: 99%
“…Recent shotgun-metagenomic sequencing of the Atlantic salmon Mycoplasma revealed that it is closely related to Mycoplasma penetrans [33,68]. It was suggested that the presence of ribo avin encoding genes and lack of pathogenicity factors in the metagenome-assembled Mycoplasma genome is indicative of a symbiotic relationship between the Mycoplasma and Atlantic salmon [68].…”
Section: Core Microbiotamentioning
confidence: 99%
“…Despite the observed dominance of Mycoplasma in salmonid hosts, very little is known about Mycoplasma and its functional potential in salmonids and other teleosts 20 . To increase knowledge of this interaction between Mycoplasma and their salmonid hosts, we present a study including three novel candidates of Mycoplasma, characterised using genome-resolved metagenomics from three different salmonid species.…”
Section: Introductionmentioning
confidence: 99%